Kufic Grammar in the Works of Ibn Taymiyyah - Rizki Gumilar; M. Hafid Mahmudi; Ebraheem Dawy (Universitas Islam Negeri Jurai Siwo Lampung, 2024)
The Kufa School significantly contributes to establishing and developing Arabic grammar. The discussions they presented attracted the attention of Ibn Taymiyyah, so their books became a primary source for him to support his opinion in the Islamic sciences. Descriptive statistical analysis was used in this research. This methodology includes collecting opinions on Kufi grammar and its special terms, and the primary source of this information is Ibn Taymiyyah’s writings on them. In support of this, his comments on these opinions and terms will also be mentioned, along with a comparison with the statements of grammarians about them. This helps in learning and teaching traditional grammar, as students can study the doctrines and compare them, which are extracted from one of the imams of scholars in the field of religious sciences. From his results, he concluded from Ibn Taymiyyah’s writings four Kufi terms in grammar and sixteen of their opinions.